Peningkatkan Motivasi dan Kemampuan Hitung Matematika dengan Problem Based Learning Berbantuan Komik (Universitas Muhammadiyah Purworejo, 2023)
The purpose of this study was to find out how to improve motivation and mathematical arithmetic ability from learning outcomes in statistic lesson through PBL with comic models for XII TKR C students of SMK Wongsorejo Gombong in 2022/2023. The research method used was classroom action research consisting of four components, namely planning, acting, observing, and reflecting. The results of the study concluded that the increase of motivation and mathematical arithmetic ability from learning outcomes through the application of PBL with comic had a positive effect. It seen by the increase from first cycle to second cycle. The student motivation in first cycle were 12,90% had weak motivation; 61,29% immediate motivation, and 25,81% had strong motivation increase to 7,32% weak motivation; 46,34% immediate motivation, and 46,34% strong motivation in second cycle. The mathematical arithmetic ability from learning outcomes in first cycle was 77,42% increase to 87,80% in second cycle.